INSTANT GRANULES OF Zingiber officinale AND Cajanus cajan LEAVES IMPROVED LIVER HISTOLOGICAL PROFILE IN DIABETIC MODEL RATS - Manalu, Johanes Marojahan; Sadiah, Siti; Aziz, Sandra Arifin; Astawan, Made; Ridwan, Taopik; Wresdiyati, Tutik (Universitas Syiah Kuala, 2025)
Diabetes mellitus can cause significant microstructural damage in liver tissue. This study evaluated the effectiveness of instant granules of Zingiber officinale and Cajanus cajan leaves on the liver histological profile in diabetic model rats. A total of 25 male Sprague Dawley rats were assigned into five groups. The group consist of negative control (NC), positive control (PC), metformin control group at a dose of 150 mg/kg BW (MET), and two treatment groups of instant granules of Z. officinale and C. cajan leaves at a dose of 300 mg/kg BW (T1) and 150 mg/kg BW (T2) for 28 days treatment. The diabetic condition was obtained by single induction of streptozotocin (35 mg/kg BW). The liver tissue was stained using hematoxylin-eosin staining to observe the cytoplasm intensity, central vein diameter, and nucleus intensity of liver cells in diabetic model rats. The results showed that administration of the instant granules significantly decrease liver microstructural damage (P0.01). The 150 mg/kg BW (T2) dose showed the most optimal effectiveness by successfully decreasing cytoplasmic intensity, reducing central vein dilation, and decreasing nuclear cell intensity. The research result indicate that instant granules have strong hepatoprotective properties that can repair liver microstructural damage caused by diabetes.